Highly efficient chemoenzymatic synthesis and facile purification of α-Gal pentasaccharyl ceramide Galα3nLc4βCer. Issue 59 (11th July 2017) - Santra, Abhishek; Li, Yanhong; Yu, Hai; Slack, Teri J.; Wang, Peng George; Chen, Xi
Abstract : α-Gal pentasaccharyl ceramide was synthesized using sequential one-pot multienzyme (OPME) systems with facile purification using a C18 cartridge followed by acylation. Abstract : A highly efficient chemoenzymatic method for synthesizing glycosphingolipids using α-Gal pentasaccharyl ceramide as an example is reported here. Enzymatic extension of the chemically synthesized lactosyl sphingosine using efficient sequential one-pot multienzyme (OPME) reactions allowed glycosylation to be carried out in aqueous solutions. Facile C18 cartridge-based quick (<30 minutes) purification protocols were established using minimal amounts of green solvents (CH3 CN and H2 O). Simple acylation in the last step led to the formation of the target glycosyl ceramide in 4 steps with an overall yield of 57%.